Project-Based Learning and Group Discussion to Enhance Critical Thinking in English Language Education: A Qualitative Case Study in SMA 1 Blora - Murtini, Anugrah; Rasyki, Adrian (Journal of English Language and Education, 2025)
This qualitative case study investigates the implementation of Project-Based Learning (PBL) combined with Group Discussion (GD) to enhance students' critical thinking skills in English language education at SMA 1 Blora. The study involved 32 students from the 11th-grade English class and was conducted in August 2025. Data were collected through classroom observations, interviews with students and teachers, and analysis of students’ project outputs. The findings indicate that integrating PBL and GD fosters higher-order thinking, improves problem-solving skills, and encourages collaborative learning. Students demonstrated increased engagement, reflective thinking, and the ability to articulate ideas coherently in English. The study concludes that PBL and GD are effective pedagogical approaches to cultivate critical thinking in secondary English education contexts.